1984
DOI: 10.1366/0003702844554738
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Fluorescence Studies of Hematoporphyrin Derivative (HPD) in Normal and Tumor Tissue of Rat

Abstract: Fluorescence studies of hematoporphyrin derivative (HPD) in normal and tumor tissue of rat were performed with nitrogen laser excitation and optical multi-channel detection. Fifteen types of tissue including inoculated tumor were investigated for rats at different delays after HPD injection. Optimum contrast functions and other criteria for discriminating tumor tissue from normal tissue are discussed. The results should have implications for practical human HPD endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…The ratio is higher for tumour than for any other of the studied organs. This is because of a decrease of the autofluorescence intensity in the tumour, as has been shown previously (Ankerst et al, 1984;Hung et al, 1991).…”
Section: Materials and Methods Chemicalssupporting
confidence: 62%
“…The ratio is higher for tumour than for any other of the studied organs. This is because of a decrease of the autofluorescence intensity in the tumour, as has been shown previously (Ankerst et al, 1984;Hung et al, 1991).…”
Section: Materials and Methods Chemicalssupporting
confidence: 62%
“…When employing HPD-PDT in liver tumours it is important to consider that normal liver tissue accumulates HPD to a very high degree (Gomer and Dougherty, 1979;Bugelski et al, 1981;Ankerst et al, 1984;Svanberg et al, 1986). For clinical use the dose-dependent transient skin sensitisation and the non-optimal light absorption profile have been considered as other obstacles.…”
mentioning
confidence: 99%
“…Fluorescence-monitoring systems for endoscopic applications 2 ' 3 normally detect the total red fluorescence in a selected wavelength band. In a recent investigation, 4 ' 5 we demonstrated that, by monitoring the full laser-induced fluorescence (LIF) spectrum and by forming simple functions of fluorescence intensities in selected wavelength bands, it is possible to achieve a strong contrast enhancement in cancer-tumor detection, which is particularly valuable when a high level of natural HPD-nonrelated LIF is present. In this Letter we show how such procedures, which were used in point measurements, can be extended to the practically and clinically more interesting case of instantaneous imaging of the tissue area under consideration.…”
mentioning
confidence: 99%
“…4 A tumor on one hind leg of white Wistar-Furth rats, induced through subcutaneous in- killed and studied, they were intravenously injected with a HPD solution (Photofrin I, ORD Inc., Cheektowaaga, New York), normally at 5 mg/kg of body weight.…”
mentioning
confidence: 99%
See 1 more Smart Citation